Training interventions to health care providers in mountainous provinces (Transport publishing house, 2007)
This publication is the fourth report in the series of lessons learnt and best practices in reproductive health supported by UNFPA in 2007. The report documents lessons learned relating to training interventions for reproductive health providers in mountainous provinces. It was published in 2007 in both English and Vietnamese.